Impact of Brewers’ Spent Grain-Containing Biscuit on Postprandial Glycaemic Response in Individuals with Metabolic Syndrome: A Crossover Randomised Controlled Trial - Xu, Yujing; Leong, Zi Ning; Zhang, Weijia; Jin, Xinrui; Kong, Jia Wen; Chan, Gregory Chung Tsing; Kim, Jung Eun (Nutrients, 2024)
Brewers’ spent grain (BSG) is a fibre and protein-rich by-product of beer-brewing. Fermenting BSG with Rhizopus oligosporus can further increase its content of soluble fibre, protein and certain antioxidants. Since nutrients rich in BSG can improve postprandial glycaemic response, this study assessed the postprandial glucose response (PPGR) and postprandial insulin response (PPIR) controlling effect of consuming 30% wheat flour substituted biscuits with autoclaved BSG (ABSG) or fermented BSG (FBSG) in individuals with metabolic syndrome (MetS). The effect on postprandial lipid panel, breath hydrogen (H2) and methane (CH4) concentration and subjective appetite response was also examined. Fifteen subjects with MetS participated in this crossover randomised controlled trial, and blood was collected at 9 time-points for 4 h after consumption of control biscuits (Control), ABSG and FBSG. A significant interaction effect was observed (Pinteraction = 0.013) for the glucose time-points concentration. At 180 min, the glucose concentration was lowered after the consumption of ABSG (p = 0.010) and FBSG (p = 0.012) compared to the Control. Moreover, the FBSG resulted in a significantly lower glucose incremental area under curve (iAUC) compared to the Control (p = 0.028). Insulin level was also lowered at 180 min after the ABSG (p = 0.010) and FBSG (p = 0.051) consumption compared to the Control. However, no difference was noted for postprandial lipid panel, breath H2 and CH4 concentration and subjective appetite response. In conclusion, the consumption of BSG-incorporated biscuits can attenuate PPGR, and fermented BSG incorporation conferred a further PPGR controlling benefit.